Preparation process of normal-temperature large-proportion recycled asphalt mixture
By mixing the waste asphalt mixture with the new album, mine powder, micro -nano -enhanced liquid and biological base additives, and perform mechanical stirring and ultrasonic treatment under normal temperature conditions, it solves the low amount of waste asphalt mixing and low performance. The problem has achieved the preparation of efficient recycled asphalt mixture and has good environmental protection benefits and performance improvement.
Patent Information
- Application Number
- CN202411460315.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In the existing preparation process for room temperature regenerated asphalt mixture, the waste asphalt mixture has low dosage, poor regeneration effect, and low performance of regenerated mixture, which limits the promotion and application of technology.
A normal-temperature large-proportion recycled asphalt mixture preparation process is adopted. The waste asphalt mixture is crushed and screened and then mixed with new aggregates, mineral powder, micro-nano strengthening liquid and bio-based additives in specific proportions, and through mechanical stirring and ultrasonic waves. treatment to evenly distribute micro-nano materials and bio-based additives, and finally compaction treatment to improve compactness and stability.
It significantly improves the amount and regeneration effect of waste asphalt mixture, enhance the performance of recycled asphalt mixture, including durability, anti -aging and high temperature stability, reducing the needs of new materials and resource mining pressure, and good environmental protection benefit.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of regenerated asphalt preparation, in particular to a process for preparing a large-proportion regenerated asphalt mixture at room temperature. Background Art
[0002] With the rapid development of highway construction, asphalt pavement will inevitably age and become damaged during use, and needs to be regularly repaired and renovated. The traditional method of asphalt pavement maintenance is mainly to remove the old material and re-lay the new material. This method not only wastes a large amount of waste asphalt mixture resources, but also increases the mining and transportation costs of new materials, and aggravates environmental pollution. Therefore, asphalt pavement regeneration technology has gradually received attention, among which room temperature regeneration technology has attracted much attention due to its advantages such as simple operation, low energy consumption, and environmental protection.
[0003] However, the current room temperature recycled asphalt mixture preparation process still faces some technical difficulties, such as low content of waste asphalt mixture, unsatisfactory recycling effect, low performance of recycled mixture, etc. These problems limit the promotion and application of room temperature recycling technology. Therefore, it is of great practical significance and broad application prospects to develop a room temperature large proportion recycled asphalt mixture preparation process to improve the content and recycling effect of waste asphalt mixture. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a room temperature large-proportion recycled asphalt mixture preparation process to solve the problems of low waste asphalt mixture dosage, unsatisfactory regeneration effect, low performance of recycled mixture in the prior art.
[0005] A process for preparing a large-proportion recycled asphalt mixture at room temperature, comprising the following steps:
[0006] Step 1: Prepare raw materials, including waste asphalt mixture accounting for 30%-80% of the total mass, new aggregate accounting for 10%-65%, mineral powder accounting for 5%-10%, as well as micro-nano enhanced liquid and bio-based additives;
[0007] Step 2: crushing the waste asphalt mixture to a particle size of less than or equal to 30 mm, and sieving to remove impurities, to obtain the crushed and sieved waste asphalt mixture;
[0008] Step 3: Evenly mix the crushed and screened waste asphalt mixture with new aggregate and mineral powder according to the proportion in step 1 to obtain a mixture;
[0009] Step 4: preparing a micro-nano strengthening liquid, wherein nano-sized silicate accounts for 0.1%-0.5% of the total mass of the strengthening liquid, is dispersed in an environmentally friendly solvent, and is surface-modified by a silane coupling agent to obtain the micro-nano strengthening liquid;
[0010] Step 5: At a temperature of 80°C to 140°C, spray the micro-nano enhanced liquid prepared in step 4 on the surface of the mixture in step 3 at a rate of 0.5% to 2% of the total mass of the waste asphalt mixture and the new aggregate, and stir mechanically for at least 10 minutes to evenly distribute the micro-nano material;
[0011] Step 6: preparing a bio-based additive, which is prepared by mixing natural vegetable oil and bio-enzymatically hydrolyzed lignin in a mass ratio of 1:1, and performing chemical modification to obtain the bio-based additive;
[0012] Step 7: Add the bio-based additive prepared in step 6 to the mixture at 1%-3% of the total mass of the waste asphalt mixture and the new aggregate, and continue stirring for at least 5 minutes until the additive is completely incorporated;
[0013] Step 8: subjecting the recycled asphalt mixture obtained in step 7 to ultrasonic treatment for 3-10 minutes to further enhance the dispersion effect of the micro-nano material and the bio-based additive;
[0014] Step nine: Perform preliminary compaction on the ultrasonically treated mixture;
[0015] Step 10: Further compact the initially compacted mixture until it reaches the density and stability required by the design.
[0016] Preferably, the environmentally friendly solvent in step 4 is water, and the particle size of the nano-silicate is less than 100 nm.
[0017] Preferably, the chemical modification treatment in step six includes heating to 60-80° C. and adding a suitable amount of acid catalyst to react to improve the activity of the bio-based additive.
[0018] Preferably, the mechanical stirring in step 5 uses a double-shaft stirrer with a stirring speed of 50-100 revolutions per minute.
[0019] Preferably, the ultrasonic treatment in step eight uses an ultrasonic device with a frequency of 20-40 kHz.
[0020] Preferably, the preliminary compaction in step nine is performed using a vibratory roller, and the number of compaction passes is 2-3 times.
[0021] Preferably, the further compaction in step ten is performed using a static roller until the Marshall stability required by the design is reached.
[0022] Preferably, the micro-nano strengthening liquid comprises nano-silicate, silane coupling agent and environmentally friendly solvent, wherein the nano-silicate accounts for 0.1%-0.5% of the total mass of the strengthening liquid, and the silane coupling agent accounts for 1%-5% of the mass of the nano-silicate.
[0023] Preferably, the bio-based additive is obtained by mixing natural vegetable oil and bio-enzymatically hydrolyzed lignin in a mass ratio of 1:1, and heating to 60-80° C. and adding an acid catalyst for chemical modification.
[0024] Compared with the prior art, the present invention has the following beneficial effects: by using a high proportion of waste asphalt mixture, the demand for new asphalt and new aggregate is significantly reduced, the pressure on the exploitation of natural resources is reduced, and at the same time, the stacking and processing costs of waste asphalt mixture are reduced, and resource recycling is achieved, which has good environmental benefits; by the introduction of micro-nano strengthening liquid and bio-based additives, the performance of recycled asphalt mixture is significantly enhanced, and micro-nano materials can improve the microstructure of asphalt, improve its durability, aging resistance and high-temperature stability; bio-based additives improve the adhesion and road performance of the mixture through their natural ingredients and chemical modification. DETAILED DESCRIPTION
[0025] Embodiment 1:
[0026] The present invention provides a process for preparing a large-proportion recycled asphalt mixture at room temperature, comprising the following steps:
[0027] Step 1: Prepare the ingredients
[0028] Waste asphalt mixture: accounts for 50% of the total mass, ensuring its source is stable and its quality is reliable.
[0029] New aggregate: accounting for 42%, select high-quality aggregate that meets the requirements.
[0030] Mineral powder: accounting for 8%, ensuring that the quality and particle size of the mineral powder meet the requirements.
[0031] Micro-nano enhanced liquid and bio-based additives: prepared according to the needs of subsequent steps.
[0032] Step 2: Crushing and screening of waste asphalt mixture
[0033] The waste asphalt mixture is put into the crusher and crushed until the particle size is less than or equal to 30mm.
[0034] Impurities such as soil and stones in the crushed material are removed through screening equipment to obtain pure crushed and screened waste asphalt mixture.
[0035] Step 3: Preparation of the mixture
[0036] According to the proportion in step one, put the crushed and screened waste asphalt mixture, new aggregate and mineral powder into the mixer.
[0037] Turn on the mixer and mix thoroughly until all the raw materials are evenly distributed to obtain a mixture.
[0038] Step 4: Preparation of micro-nano enhanced solution
[0039] Environmentally friendly solution water is selected, and the amount of nano-silicate required is calculated so that it accounts for 0.3% of the total mass of the strengthening solution.
[0040] Nano-silicate is dispersed in water and surface-modified by a silane coupling agent to obtain a micro-nano enhanced liquid. The amount of the silane coupling agent used is 3% of the mass of the nano-silicate.
[0041] Step 5: Spraying and stirring of micro-nano strengthening liquid
[0042] At a temperature of 110° C., the micro-nano enhanced liquid prepared in step 4 is sprayed on the surface of the mixture in step 3 according to 1% of the total mass of the waste asphalt mixture and the new aggregate.
[0043] The mixture was stirred with a double-shaft mixer at a speed of 75 revolutions per minute for at least 10 minutes to ensure that the micro-nano materials were evenly distributed in the mixture.
[0044] Step 6: Preparation of bio-based additives
[0045] Natural vegetable oil and bio-enzymatic lignin are mixed in a mass ratio of 1:1.
[0046] The mixture is heated to 70° C., and an appropriate amount of an acid catalyst is added to react to improve the activity of the bio-based additive. After the reaction is completed, the bio-based additive is obtained.
[0047] Step 7: Addition and mixing of bio-based additives
[0048] The bio-based additive prepared in step six is added to the mixture at 2% of the total mass of the waste asphalt mixture and the new aggregate.
[0049] Continue stirring with the twin-shaft mixer at a constant stirring speed for at least 5 minutes until the additive is completely incorporated into the mixture.
[0050] Step 8: Ultrasonic treatment
[0051] The regenerated asphalt mixture obtained in step seven is placed in an ultrasonic treatment device and treated with ultrasonic waves at a frequency of 30 kHz for 5 minutes to further enhance the dispersion effect of the micro-nano materials and bio-based additives.
[0052] Step 9: Initial compaction
[0053] A vibratory roller is used to carry out preliminary compaction of the ultrasonically treated mixture twice to ensure that the mixture is initially formed.
[0054] Step 10: Further compaction
[0055] The initially compacted mixture is moved to a static roller for further compaction until the required Marshall stability and density are achieved.
[0056] Note: Normal temperature in the present invention refers to a range of 20 to 40 degrees lower than the mixing temperature of traditional warm mix agents, and the mixing temperature of traditional warm mix agents in the present invention is between 120°C and 160°C, so normal temperature in the present invention refers to a temperature of 80°C to 140°C.
[0057] Embodiment 2:
[0058] The present invention provides a process for preparing a large-proportion recycled asphalt mixture at room temperature, comprising the following steps:
[0059] Step 1: Prepare the ingredients
[0060] Waste asphalt mixture: accounts for 30% of the total mass, ensuring its source is stable and its quality is reliable.
[0061] New aggregate: 65%, select high-quality aggregate that meets the requirements.
[0062] Mineral powder: 5%, ensuring that the quality and particle size of the mineral powder meet the requirements.
[0063] Micro-nano enhanced liquid and bio-based additives: prepared according to the needs of subsequent steps.
[0064] Step 2: Crushing and screening of waste asphalt mixture
[0065] The waste asphalt mixture is put into the crusher and crushed until the particle size is less than or equal to 30mm.
[0066] Impurities such as soil and stones in the crushed material are removed through screening equipment to obtain pure crushed and screened waste asphalt mixture.
[0067] Step 3: Preparation of the mixture
[0068] According to the proportion in step one, put the crushed and screened waste asphalt mixture, new aggregate and mineral powder into the mixer.
[0069] Turn on the mixer and mix thoroughly until all the raw materials are evenly distributed to obtain a mixture.
[0070] Step 4: Preparation of micro-nano enhanced solution
[0071] Environmentally friendly solution water is selected, and the amount of nano-silicate required is calculated so that it accounts for 0.1% of the total mass of the strengthening solution.
[0072] Nano-silicate is dispersed in water and surface-modified by a silane coupling agent to obtain a micro-nano enhanced liquid. The amount of the silane coupling agent used is 1% of the mass of the nano-silicate.
[0073] Step 5: Spraying and stirring of micro-nano strengthening liquid
[0074] At a temperature of 80° C., the micro-nano enhanced liquid prepared in step 4 is sprayed on the surface of the mixture in step 3 at 0.5% of the total mass of the waste asphalt mixture and the new aggregate.
[0075] The mixture is stirred with a double-shaft mixer at a speed of 50 revolutions per minute for at least 10 minutes to ensure that the micro-nano materials are evenly distributed in the mixture.
[0076] Step 6: Preparation of bio-based additives
[0077] Natural vegetable oil and bio-enzymatic lignin are mixed in a mass ratio of 1:1.
[0078] The mixture is heated to 60° C., and an appropriate amount of an acid catalyst is added to react to improve the activity of the bio-based additive. After the reaction is completed, the bio-based additive is obtained.
[0079] Step 7: Addition and mixing of bio-based additives
[0080] The bio-based additive prepared in step six is added to the mixture at 1% of the total mass of the waste asphalt mixture and the new aggregate.
[0081] Continue stirring with the twin-shaft mixer at a constant stirring speed for at least 5 minutes until the additive is completely incorporated into the mixture.
[0082] Step 8: Ultrasonic treatment
[0083] The regenerated asphalt mixture obtained in step seven is placed in an ultrasonic treatment device and treated with ultrasonic waves at a frequency of 20 kHz for 3 minutes to further enhance the dispersion effect of the micro-nano materials and bio-based additives.
[0084] Step 9: Initial compaction
[0085] A vibratory roller is used to carry out preliminary compaction of the ultrasonically treated mixture twice to ensure that the mixture is initially formed.
[0086] Step 10: Further compaction
[0087] The initially compacted mixture is moved to a static roller for further compaction until the required Marshall stability and density are achieved.
[0088] Embodiment 3
[0089] The present invention provides a process for preparing a large-proportion recycled asphalt mixture at room temperature, comprising the following steps:
[0090] Step 1: Prepare the ingredients
[0091] Waste asphalt mixture: accounts for 80% of the total mass, ensuring its source is stable and its quality is reliable.
[0092] New aggregate: 10%, select high-quality aggregate that meets the requirements.
[0093] Mineral powder: 10%, ensuring that the quality and particle size of the mineral powder meet the requirements.
[0094] Micro-nano enhanced liquid and bio-based additives: prepared according to the needs of subsequent steps.
[0095] Step 2: Crushing and screening of waste asphalt mixture
[0096] The waste asphalt mixture is put into the crusher and crushed until the particle size is less than or equal to 30mm.
[0097] Impurities such as soil and stones in the crushed material are removed through screening equipment to obtain pure crushed and screened waste asphalt mixture.
[0098] Step 3: Preparation of the mixture
[0099] According to the proportion in step one, put the crushed and screened waste asphalt mixture, new aggregate and mineral powder into the mixer.
[0100] Turn on the mixer and mix thoroughly until all the raw materials are evenly distributed to obtain a mixture.
[0101] Step 4: Preparation of micro-nano enhanced solution
[0102] Environmentally friendly solution water is selected, and the amount of nano-silicate required is calculated so that it accounts for 0.5% of the total mass of the strengthening solution.
[0103] Nano-silicate is dispersed in water and surface-modified by a silane coupling agent to obtain a micro-nano enhanced liquid. The amount of the silane coupling agent used is 5% of the mass of the nano-silicate.
[0104] Step 5: Spraying and stirring of micro-nano strengthening liquid
[0105] At a temperature of 140° C., the micro-nano enhanced liquid prepared in step 4 is sprayed on the surface of the mixture in step 3 at 2% of the total mass of the waste asphalt mixture and the new aggregate.
[0106] The mixture is stirred with a double-shaft mixer at a speed of 100 revolutions per minute for at least 10 minutes to ensure that the micro-nano material is evenly distributed in the mixture.
[0107] Step 6: Preparation of bio-based additives
[0108] Natural vegetable oil and bio-enzymatic lignin are mixed in a mass ratio of 1:1.
[0109] The mixture is heated to 80°C, and an appropriate amount of an acid catalyst is added to react to improve the activity of the bio-based additive. After the reaction is completed, the bio-based additive is obtained.
[0110] Step 7: Addition and mixing of bio-based additives
[0111] The bio-based additive prepared in step six is added to the mixture at 3% of the total mass of the waste asphalt mixture and the new aggregate.
[0112] Continue stirring with the twin-shaft mixer at a constant stirring speed for at least 5 minutes until the additive is completely incorporated into the mixture.
[0113] Step 8: Ultrasonic treatment
[0114] The regenerated asphalt mixture obtained in step seven is placed in an ultrasonic treatment device and treated with ultrasonic waves at a frequency of 40 kHz for 10 minutes to further enhance the dispersion effect of the micro-nano materials and bio-based additives.
[0115] Step 9: Initial compaction
[0116] A vibratory roller is used to carry out preliminary compaction of the ultrasonically treated mixture twice to ensure that the mixture is initially formed.
[0117] Step 10: Further compaction
[0118] The initially compacted mixture is moved to a static roller for further compaction until the required Marshall stability and density are achieved.
[0119] Embodiment 4
[0120] The present invention provides a process for preparing a large-proportion recycled asphalt mixture at room temperature, comprising the following steps:
[0121] Step 1: Prepare the ingredients
[0122] Waste asphalt mixture: accounts for 47% of the total mass, ensuring its source is stable and its quality is reliable.
[0123] New aggregate: accounting for 47%, select high-quality aggregate that meets the requirements.
[0124] Mineral powder: accounting for 6%, ensuring that the quality and particle size of the mineral powder meet the requirements.
[0125] Micro-nano enhanced liquid and bio-based additives: prepared according to the needs of subsequent steps.
[0126] Step 2: Crushing and screening of waste asphalt mixture
[0127] The waste asphalt mixture is put into the crusher and crushed until the particle size is less than or equal to 30mm.
[0128] Impurities such as soil and stones in the crushed material are removed through screening equipment to obtain pure crushed and screened waste asphalt mixture.
[0129] Step 3: Preparation of the mixture
[0130] According to the proportion in step one, put the crushed and screened waste asphalt mixture, new aggregate and mineral powder into the mixer.
[0131] Turn on the mixer and mix thoroughly until all the raw materials are evenly distributed to obtain a mixture.
[0132] Step 4: Preparation of micro-nano enhanced solution
[0133] Environmentally friendly solution water is selected, and the amount of nano-silicate required is calculated so that it accounts for 0.4% of the total mass of the strengthening solution.
[0134] Nano-silicate is dispersed in water and surface-modified by a silane coupling agent to obtain a micro-nano enhanced liquid. The amount of the silane coupling agent used is 4% of the mass of the nano-silicate.
[0135] Step 5: Spraying and stirring of micro-nano strengthening liquid
[0136] At a temperature of 140° C., the micro-nano enhanced liquid prepared in step 4 is sprayed on the surface of the mixture in step 3 at 2% of the total mass of the waste asphalt mixture and the new aggregate.
[0137] The mixture is stirred with a double-shaft mixer at a speed of 80 revolutions per minute for at least 10 minutes to ensure that the micro-nano material is evenly distributed in the mixture.
[0138] Step 6: Preparation of bio-based additives
[0139] Natural vegetable oil and bio-enzymatic lignin are mixed in a mass ratio of 1:1.
[0140] The mixture is heated to 80°C, and an appropriate amount of an acid catalyst is added to react to improve the activity of the bio-based additive. After the reaction is completed, the bio-based additive is obtained.
[0141] Step 7: Addition and mixing of bio-based additives
[0142] The bio-based additive prepared in step six is added to the mixture at 3% of the total mass of the waste asphalt mixture and the new aggregate.
[0143] Continue stirring with the twin-shaft mixer at a constant stirring speed for at least 5 minutes until the additive is completely incorporated into the mixture.
[0144] Step 8: Ultrasonic treatment
[0145] The regenerated asphalt mixture obtained in step seven is placed in an ultrasonic treatment device and treated with ultrasonic waves at a frequency of 40 kHz for 3-10 minutes to further enhance the dispersion effect of the micro-nano materials and bio-based additives.
[0146] Step 9: Initial compaction
[0147] A vibratory roller is used to carry out preliminary compaction of the ultrasonically treated mixture twice to ensure that the mixture is initially formed.
[0148] Step 10: Further compaction
[0149] The initially compacted mixture is moved to a static roller for further compaction until the required Marshall stability and density are achieved.
[0150] According to the different ultrasonic treatment time, the following experimental table is obtained:
[0151]
[0152] Experimental analysis:
[0153] Effect of ultrasonic treatment time on Marshall stability:
[0154] From the experimental data, it can be seen that with the increase of ultrasonic treatment time, the Marshall stability shows a trend of increasing first and then stabilizing. The Marshall stability of experimental groups B, C, and D is higher than that of the control group, indicating that ultrasonic treatment does help to improve the cohesion and stability of the mixture.
[0155] The Marshall stability of experimental group C (7 minutes treatment time) reached the highest value, while the stability of experimental group D (10 minutes treatment time) decreased slightly, but was still higher than the control group. This may indicate that increasing the ultrasonic treatment time within a certain range can significantly improve the performance of the mixture, but too long a treatment time may no longer produce additional positive effects and may even slightly reduce the performance due to overtreatment.
[0156] Effect of ultrasonic treatment time on rutting depth:
[0157] The rutting depth data show that as the ultrasonic treatment time increases, the rutting depth gradually decreases, but after the treatment time exceeds a certain value (such as experimental group C to D), the reduction is no longer significant. This further supports the view that ultrasonic treatment helps improve the ability of the mixture to resist permanent deformation.
[0158] The rutting depths of experimental groups C and D were similar and both lower than that of the control group, indicating that the anti-rutting performance of the mixture was effectively improved at these two treatment times.
[0159] Effect of ultrasonic treatment time on water damage resistance:
[0160] The water damage resistance (expressed as residual stability) increased with the increase of ultrasonic treatment time, but there was little difference between experimental groups C and D. This shows that ultrasonic treatment can enhance the water damage resistance of the mixture, but after the treatment time exceeds a certain value (such as 7 minutes), the effect of improving the water damage resistance may tend to saturation.
[0161] The residual stability of experimental groups C and D was higher than that of the control group, and was close to or exceeded 90%, indicating that ultrasonic treatment was of great significance in improving the durability of the mixture.
[0162] In summary, the ultrasonic treatment time has a significant effect on the performance of large-proportion recycled asphalt mixtures at room temperature. Increasing the ultrasonic treatment time within a certain range can significantly improve the Marshall stability of the mixture, reduce the rutting depth, and improve the water damage resistance. However, when the treatment time exceeds a certain value (such as 7 minutes in this experiment), the performance improvement may tend to saturation or slightly decrease. Therefore, in practical applications, the appropriate ultrasonic treatment time should be selected according to the specific material composition and performance requirements.
[0163] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. "Multiple" means two or more, unless otherwise clearly and specifically defined.
[0164] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0165] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0166] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0167] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing a large proportion of recycled asphalt mixture at room temperature, characterized in that: The following steps are involved: Step 1: Prepare raw materials, including waste asphalt mixture accounting for 30%-80% of the total mass, new aggregate accounting for 10%-65%, mineral powder accounting for 5%-10%, as well as micro-nano enhanced liquid and bio-based additives; Step 2: crushing the waste asphalt mixture to a particle size of less than or equal to 30 mm, and sieving to remove impurities, to obtain the crushed and sieved waste asphalt mixture; Step 3: Evenly mix the crushed and screened waste asphalt mixture with new aggregate and mineral powder according to the proportion in step 1 to obtain a mixture; Step 4: preparing a micro-nano strengthening liquid, wherein nano-sized silicate accounts for 0.1%-0.5% of the total mass of the strengthening liquid, is dispersed in an environmentally friendly solvent, and is surface-modified by a silane coupling agent to obtain the micro-nano strengthening liquid; Step 5: At a temperature of 80°C to 140°C, spray the micro-nano enhanced liquid prepared in step 4 on the surface of the mixture in step 3 at a rate of 0.5% to 2% of the total mass of the waste asphalt mixture and the new aggregate, and stir mechanically for at least 10 minutes to evenly distribute the micro-nano material; Step 6: preparing a bio-based additive, which is prepared by mixing natural vegetable oil and bio-enzymatically hydrolyzed lignin in a mass ratio of 1:1, and performing chemical modification to obtain the bio-based additive; Step 7: Add the bio-based additive prepared in step 6 to the mixture at 1%-3% of the total mass of the waste asphalt mixture and the new aggregate, and continue stirring for at least 5 minutes until the additive is completely incorporated; Step 8: subjecting the recycled asphalt mixture obtained in step 7 to ultrasonic treatment for 3-10 minutes to further enhance the dispersion effect of the micro-nano material and the bio-based additive; Step nine: Perform preliminary compaction on the ultrasonically treated mixture; Step 10: Further compact the initially compacted mixture until it reaches the density and stability required by the design.
2. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 1, characterized in that: The environmentally friendly solvent in step 4 is water, and the particle size of the nano-silicate is less than 100 nm.
3. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 2, characterized in that: The chemical modification treatment in step six includes heating to 60-80° C. and adding an appropriate amount of acid catalyst to react to improve the activity of the bio-based additive.
4. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 3, characterized in that: The mechanical stirring in step 5 uses a double-shaft mixer with a stirring speed of 50-100 revolutions per minute.
5. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 4, characterized in that: The ultrasonic treatment in step eight uses an ultrasonic device with a frequency of 20-40 kHz.
6. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 5, characterized in that: The initial compaction in step nine is carried out using a vibratory roller, with 2-3 compaction passes.
7. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 1, characterized in that: Further compaction in step 10 is carried out using a static roller until the required Marshall stability is achieved.
8. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 7, characterized in that: The micro-nano strengthening liquid comprises nano-scale silicate, silane coupling agent and environmentally friendly solvent, wherein the nano-scale silicate accounts for 0.1%-0.5% of the total mass of the strengthening liquid, and the silane coupling agent accounts for 1%-5% of the mass of the nano-scale silicate.
9. A process for preparing a large proportion of recycled asphalt mixture at room temperature as claimed in claim 8, characterized in that: The bio-based additive is obtained by mixing natural vegetable oil and bio-enzymatically hydrolyzed lignin in a mass ratio of 1:1, and heating to 60-80° C. and adding an acid catalyst for chemical modification.
Citation Information
Patent Citations
Regeneration field mixed asphalt and preparation method thereof
CN104446158A
Composite environment-friendly asphalt interface regenerant with high viscosity and toughness and semi-fusion function and preparation method of same
CN111944321A
Modified regenerant as well as preparation method and application thereof
CN116285198A
Recycled asphalt mixture manufacturing method and recycled asphalt mixture
JP2020037798A
Warm recycled asphalt additives, manufacturing method thereof and warm recycled asphalt concrete
KR101641687B1